The Association between Family and Parental Factors and Obesity among Children in Nanchang, China - Zhang, Peng; Wu, Hongjiao; Zhou, Xiaojun; Lu, Yuanan; Yuan, Zhaokang; Moore, Justin B.; Maddock, Jay E. (Frontiers in Public Health, 2016)
Background With rapid economic development in China, traditional patterns of health behaviors are changing, concurrent with a rise in childhood obesity. While the home environment and parenting behaviors are modifiable factors that could be targeted for intervention, little is known about their relationship with children’s health behaviors. Therefore, the purpose of this study was to investigate the relationship between obesity and home and parenting factors in Chinese children. Methods A cross-sectional survey was conducted in Nanchang, China in 2013 with caregivers (N = 470) of a child between the ages of 2 and 10 years. Regression analyses were conducted to determine risk factors for childhood obesity. Results Obesity prevalence (21.7%) did not differ by demographic variables. Eight physical activity, nutrition, and sedentary variables had significant relationships to obesity status. Logistic regression analysis revealed three significant predictors of obesity: the number of days the family eats meals together (odds ratio = 0.84, 95% CI 0.73–0.96) and parental home computer use time (odds ratio = 0.83, 95% CI 0.72–0.96) were related to lower levels of obesity, while parental television time (odds ratio = 1.25 95% CI 1.07–1.47) was related to higher levels of obesity. Conclusion The prevalence of obesity among children is high in Nanchang. Family and environmental risk factors are significantly related to obesity.